Oral bacteria detection among children with cancer in a tertiary teaching hospital in Kuala Lumpur, Malaysia - Sidi, Omar; S., F.N.; Romano, Ngui; Ab, Rahman; S., Z.; Foo, J.C.; Wang, Q.Y; Hassan, N.A.; Lim, Y.A.L.; Musa, S. (Malaysian Society of Parasitology and Tropical Medicine, 2021)
This study sought to determine the prevalence of pathogenic and non-pathogenic bacteria in the oral cavities of children with cancer. There were 68 paediatric patients with cancer who were included in this study. Oral swab samples from the dorsum of tongues and mouth floors of these patients were subjected to culture, staining, and molecular methods to detect the bacteria. The overall prevalence of gram-positive and gram-negative bacteria was 79.4% (54/68; 95% CI = 68.4 – 87.3) and 25% (17/68; 95% CI = 16.2 – 36.4), respectively. Streptococcus salivarius and Streptococcus parasanguinis were the predominant pathogenic grampositive bacteria, while Neisseria subflava and Neisseria perflava were the most common pathogenic gram-negative bacteria. The results revealed that the number of bacteria isolates recovered in patients receiving cancer treatment was higher (55.9%) than those who had not received treatment (16.2%). Therefore, more isolated pathogenic bacteria were observed post-therapy (54.4%). Pathogenic organisms can have significant implications on patient health. Awareness of the types of bacteria inhabiting the oral cavity is essential to predict and prevent dental problems, and their associated systemic complications. Findings on the diversity of oral microflora can also provide a better understanding of the aetiology of oral diseases in paediatric patients receiving cancer treatment.